Comparison of trained and untrained girls' blood buffering capacity response to three types of recovery during Repeated High-Intensity endurance test - Mahtab Tavakoli; Seyed Mohamad Marandi; Mehdi Kargar Fard; Behzad Pakrad; Arash Dehghan (Journal of Sport & Exercise Physiology (JSEP) / Fīziyuluzhī-i Varzish va Fa̒āliyyat-i Badanī, 2021)
Purpose: Recovery after intense interval training plays an important role in improving athletic performance, while the type of recovery and exercise background can affect athletic performance. The aim of this study was to compare the Response of blood buffering capacity to three types of recovery during Repeated High-Intensity endurance test in trained and untrained girls' students of Farhangian University.Methods: 30 female students of Farhangian University (mean age 22.49 ±.3 (year), weight 68.33 ± 7.31 (kg) and height 176.76 ± 8.32 (cm) were randomly selected in three recovery groups (active: N=10, passive: N=10, Stretching: N=10) randomly. The Subjects underwent three types of recovery during the repeated high-intensity endurance test after evaluating the maximum oxygen consumption according to a specific pattern in a crossover methods, three days in a week. Arterial blood sample were taken measured before and immediately after the test and buffering capacity and carnosine were analyzed by ABG and ELISA techniques. After 8-eight weeks of aerobic exercise (65-80% of maximal heart rate), the test and blood sampling were repeated with the same pre-test and at the same time.Results: In untrained girls, only significant difference was found between stretching and active recovery for oxygen saturation, and in trained girls' there was a significant increase in oxygen saturation for active and passive recovery. Significant increase in blood acidity, bicarbonate, base buffers and carnosine was observed in trained girls by active recovery (P ≤ 0.05).Conclusion: The results show that the response of buffering capacity to the three types of recovery was significantly higher in trained subjects. Which is more notable with active recovery.